Exosomes from mesenchymal stem cells overexpressing MIF enhance myocardial repair. Issue 11 (20th January 2020) - Liu, Xiaolin; Li, Xin; Zhu, Wenwu; Zhang, Yuelin; Hong, Yimei; Liang, Xiaoting; Fan, Baohan; Zhao, Hongyan; He, Haiwei; Zhang, Fengxiang
Abstract: Accumulating evidence has shown that mesenchymal stem cell (MSC)‐derived exosomes (exo) mediate cardiac repair following myocardial infarction (MI). Macrophage migration inhibitory factor (MIF), a proinflammatory cytokine, plays a critical role in regulating cell homeostasis. This study aimed to investigate the cardioprotective effects of exo secreted from bone marrow‐MSCs (BM‐MSCs) overexpressing MIF in a rat model of MI. MIF plasmid was transducted in BM‐MSCs. Exo were isolated from the supernatants of BM‐MSCs and MIF‐BM‐MSCs, respectively. The morphology of mitochondria in neonatal mice cardiomyocytes (NRCMs) was determined by MitoTracker staining. The apoptosis of NRCMs was examined by deoxynucleotidyl transferase‐mediated dUTP nick end‐labeling. BM‐MSC‐exo and MIF‐BM‐MSC‐exo were intramuscularly injected into the peri‐infarct region in a rat model of MI. The heart function of rats was assessed by echocardiography. The expression of MIF was greatly enhanced in MIF‐BM‐MSCs compared with BM‐MSCs. Both BM‐MSC‐exo and MIF‐BM‐MSC‐exo expressed CD63 and CD81. NRCMs treated with MIF‐BM‐MSC‐exo exhibited less mitochondrial fragmentation and cell apoptosis under hypoxia/serum deprivation (H/SD) challenge than those treated with BM‐MSC‐exo via activating adenosine 5′‐monophosphate‐activated protein kinase signaling. Moreover, these effects were partially abrogated by Compound C. Injection of BM‐MSC‐exo or MIF‐BM‐MSC‐exo greatly restored heart function in a rat model of MI. Compared with BM‐MSC‐exo, injection of MIF‐BM‐MSC‐exo was associated with enhanced heart function, reduced heart remodeling, less cardiomyocyte mitochondrial fragmentation, reactive oxygen species generation, and apoptosis. Our study reveals a new mechanism of MIF‐BM‐MSC‐exo‐based therapy for MI and provides a novel strategy for cardiovascular disease treatment. Abstract : Migration inhibitory factor (MIF)‐bone marrow (BM)‐mesenchymal stem cell (MSC)‐exosome (exo) attenuated hypoxia and serum deprivation‐induced cardiomyocyte injury via inhibition of mitochondrial fragmentation. Injection of MIF‐BM‐MSC‐exo restored heart function by inhibiting mitochondrial fragmentation and apoptosis in a rat model of myocardial infarction. MSC‐exo represents a novel strategy for cardioprotection and MIF engineering MSCs can augment their therapeutic efficacy in regenerative medicine.